2021
DOI: 10.1159/000514592
|View full text |Cite
|
Sign up to set email alerts
|

Multicolor-FISH Characterization of a Prenatal Mosaicism for a Chromosomal Rearrangement Undetected by Molecular Cytogenetics

Abstract: Fetal mosaicism for chromosomal rearrangements remains a challenge to diagnose, even in the era of whole-genome sequencing. We present here a case of fetal mosaicism for a chromosomal rearrangement explored in amniocytes and fetal muscle, consisting of a major cell population (95%) with partial monosomy 4q and a minor population (5%) with additional material replacing the 4qter deleted segment. Molecular techniques (MLPA, array-CGH) failed to assess the origin of this material. Only multicolor-FISH identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…FISH analysis, especially for the diagnosis of complex chromosome abnormalities, has set up a bridge between chromosome banding technology and molecular genetics [ 18 ]. Additionally, previous studies have demonstrated that FISH analysis can identify low-level mosaicism [ 19 ] and mosaicism for chromosomal rearrangement undetected by molecular cytogenetics [ 20 ]. Correspondingly, the combination of G-banding and FISH provides an efficient method for prenatal and postnatal chromosomal analysis [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…FISH analysis, especially for the diagnosis of complex chromosome abnormalities, has set up a bridge between chromosome banding technology and molecular genetics [ 18 ]. Additionally, previous studies have demonstrated that FISH analysis can identify low-level mosaicism [ 19 ] and mosaicism for chromosomal rearrangement undetected by molecular cytogenetics [ 20 ]. Correspondingly, the combination of G-banding and FISH provides an efficient method for prenatal and postnatal chromosomal analysis [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even if NAHR is prone to generating tandem duplications, rarer anomalies can be dismissed using FISH (inserted duplication, cryptic translocation etc.). Moreover, FISH performs better than CMA in detecting low rates of mosaicism (Mary et al 2021), which is of importance for genetic counselling. Finally, FISH is a targeted analysis and avoids incidental, nondesirable genomic imbalance findings among apparently healthy parents.…”
Section: Shedding Light On Phenotypical Variabilitymentioning
confidence: 99%